2019
DOI: 10.1002/pd.5437
|View full text |Cite
|
Sign up to set email alerts
|

Expanded carrier screening for autosomal recessive conditions in health care: Arguments for a couple‐based approach and examination of couples' views

Abstract: Background Expanded carrier screening (ECS) is aimed at detecting carrier states for autosomal recessive (AR) or X‐linked conditions in couples from the general population planning a pregnancy. ECS is currently usually offered on an individual basis despite the fact that, for AR conditions, only carrier couples are at risk of affected offspring. In this paper, we present a couple‐based ECS test‐offer for AR conditions, where results are offered as couple‐results only, and describe how couples view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 25 publications
2
28
0
1
Order By: Relevance
“…Publicly funded population RCS globally is tending towards reporting couple‐based findings. Evidence suggests that participants understand and accept this approach and that it is feasible as a population screening model 5,13,16. Mackenzie's Mission participants will be informed when they both carry the same disease‐causing variant for an autosomal recessive condition, or when the genetic mother is found to carry one of the X‐linked conditions screened for.…”
Section: Reporting Results: Ethical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Publicly funded population RCS globally is tending towards reporting couple‐based findings. Evidence suggests that participants understand and accept this approach and that it is feasible as a population screening model 5,13,16. Mackenzie's Mission participants will be informed when they both carry the same disease‐causing variant for an autosomal recessive condition, or when the genetic mother is found to carry one of the X‐linked conditions screened for.…”
Section: Reporting Results: Ethical Implicationsmentioning
confidence: 99%
“…Any potential for false reassurance can be carefully addressed during the pre‐ and post‐test education processes. Pragmatically, publicly funded RCS would be prohibitively expensive to offer if it reported individual carrier results, as the majority of individuals screened are likely to be a carrier for something 16. Each of these people would then need individual follow‐up, despite their future offspring having a very low chance of actually having that autosomal recessive condition, even if they were to re‐partner 17…”
Section: Reporting Results: Ethical Implicationsmentioning
confidence: 99%
“…The size of the gene panel also imposes potential technical constraints, in terms of the requirement to analyze and report large numbers of variants. For this study, the use of a couples-based approach to analysis, with autosomal variants reported only if both partners carry a variant that meets reporting criteria, means that the burden of analysis is markedly reduced compared with reporting individual variant information, removing this as a constraint on panel design [14,15]. A couples-based approach also greatly reduces the genetic counseling requirements for the study [16].…”
Section: Technical Considerationsmentioning
confidence: 99%
“…To date, attention in the literature has centred on the attitudes of patients and families of those affected by genetic conditions, [3][4][5] hypothetical views of HCPs on whether screening should be offered 6 and the cost effectiveness of RGCS. 7,8 While these elements are important, they do not inform us about how to implement a RGCS programme.…”
Section: Introductionmentioning
confidence: 99%